Green Sukuk dalam Perspektif Tafsir Tematik: Implementasi Prinsip Lā Tufsidu fil Arḍ dalam Ekonomi Syariah Kontemporer - Nabila Aulia Putri Hrp; Nurhayati; Yenni Samri Juliati Nasution (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the relevance of the principle of lā tufsidu fil ardḍ in the Qur'an to the development of green sukuk as a sustainable Islamic financial instrument. Using a maudhu'i tafsir approach and qualitative-descriptive analysis, this study finds that the prohibition of earth destruction and the mandate of the caliphate serve as the theological basis for green financial practices in Islam. Green sukuk has been proven to support the financing of environmentally friendly projects such as renewable energy, forest conservation, and public transportation and has the potential to be strengthened through the integration of digital technology. This study emphasizes the novelty of combining tafsir studies with modern financial analysis and shows that green sukuk is a concrete implementation of maqāṣid al-shari'ah in environmental protection